2021
DOI: 10.1108/tg-01-2021-0002
|View full text |Cite
|
Sign up to set email alerts
|

An interaction effect of perceived government response on COVID-19 and government agency’s use of ICT in building trust among citizens of Pakistan

Abstract: Purpose Among the digital age players, one of the fastest-growing digital channels is social media. In the past few years, developing nations’ government entities and political parties started using social media platforms to broadcast important information regarding decisions made at the state level. Pakistan is among those countries. Therefore, this study aims to empirically investigate the impact of the government agency’s provision of quality information on social media in establishing trust among citizens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 33 publications
(42 reference statements)
1
18
0
1
Order By: Relevance
“…Perceived government response on Covid-19 represents the prompt and timely response of the government during the pandemic (Mansoor, 2021b) that helped control the pandemic (Pabbajah et al, 2020). Those citizens who felt confident in the government measures and actions while fighting with the Covid-19 possess greater trust in the government (Pabbajah et al, 2020).…”
Section: Interactions With Government Officials On Sns Perceived Government Response To Covid-19 Perceived E-governance Effectiveness Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceived government response on Covid-19 represents the prompt and timely response of the government during the pandemic (Mansoor, 2021b) that helped control the pandemic (Pabbajah et al, 2020). Those citizens who felt confident in the government measures and actions while fighting with the Covid-19 possess greater trust in the government (Pabbajah et al, 2020).…”
Section: Interactions With Government Officials On Sns Perceived Government Response To Covid-19 Perceived E-governance Effectiveness Andmentioning
confidence: 99%
“…Communication has been considered a meaningful way to decrease uncertainty and anxiety levels among people (Royo-Vela & McBee, 2020). Hence, communication of timely and accurate information by the government officials using Social Networking Sites (SNS) with the public during natural hazards and crises may help maintain public trust in government (Mansoor, 2021b). Notably, during the current pandemic, the government officials of many countries actively communicated with their public via SNS to keep them updated, resulting in a sense of security among them (Wong et al, 2020).…”
mentioning
confidence: 99%
“…Moreover, researchers suggested that perceived transparency leads to increased public trust in government (Mansoor, 2021a;Moreno-Albarracı ´n et al, 2020). While overall public trust is based on fairness and expectation from the authorities that make decisions to safeguard people's welfare (Houston and Harding, 2013) and technology can aid in making this information accessible to the public.…”
Section: The Mediating Role Of Perceived Effectiveness Of E-governancementioning
confidence: 99%
“…Besides, the measure's convergent and discriminant validity was assessed. For stoicism and two items, i.e., ST8 and ST11, and for physical fatigue, two items, i.e., PF3 and PF12 with factor loadings less than 0.5, were excluded from the analysis as per instructions of Hair et al (2012) based on their high impact on AVE and the reliability of the whole construct (Mansoor, 2021b). As the factor loadings of all other indicator variables were in the range with a significant loading of each item (p < 0.001) onto its underlying variable and the AVE of latent variables was above 0.50 for all study constructs, convergent validity was established (Hair et al, 2010;Noor et al, 2021).…”
Section: Assessing the Measurement Modelmentioning
confidence: 99%